The effectiveness of professional training programs for school administrators in Muscat, Oman / Humaid Salem Hamdan Alhajri - Alhajri, Humaid Salem Hamdan (2013)
The purpose of this study was to analyze the efficiency of professional training programs (PTP) organized by the Muscat Governorate of Education in Oman for school administrators from the perspective of program improvement. The study identifies the opportunities for participation in professional training programs for school administrators for the following reasons: to improve their performance at schools, to determine the level of effectiveness of professional training programs, to develop skills, to enhance ability and attitude, to analyze the constraints that hinders the effectiveness of PTP, to improve qualifications and occupations, and finally, to suggest the improvements of PTP for school administrators. This research utilized mixed method research approaches qualitative and quantitative methods of data collection and analysis to provide valid and more reliable research findings. Qualitative data were gathered from interviews, while quantitative data were collected using a questionnaire. The respondents of the questionnaire were all principals and assistant principals in the Muscat Governorate of Education. A total of 215 questionnaires were completed and returned by respondents (77 male and 138 female), and 13 participants were selected for interviews. The conceptual framework was based on the Goal – attainment approach, system approach of the organization effectiveness theory, and Macro training and training model by Al- Khayyat and El-Gamal (1997). The literature review indicated that there were a number of training programs implemented for school administrators (Ministry of Education, 2010). The findings of this research indicated that the majority of participants felt that professional training program is resourceful and significant. At the same time, they requested organizers to be more concerned when implementing PTP. Another significant finding indicated that the opportunities for participating in national and international conferences and exchanging visits outside the region were considered crucial among administrators. On the availability of the program, the finding indicated that there were significant differences in favor of female participants. Furthermore, the findings show that the participants felt that the planning of PTP could be improved in many aspects; such as, training needs analysis procedure, trainers’ efficiency, and long term plans for PTP. On the other hand, the PTP faces many challenges; such as: how to relate theoretical to the practical aspect in development programs, the restrictive nature of exchange visits, assessing student learning or the specification of the programs and the targeted staff in the PTP, and meetings do not provide solutions to educational issues. As the lack of cooperation between departments in conveying knowledge, skills to school principals; trainers are inefficient and the method of preparing the work papers is not realistic. Finally, the findings had a number of implications for the development of PTP for school administrators. For this reason, some areas need improvement in order to enhance the effectiveness level of knowledge, skills and abilities of school administrators in the future.